Diallec analysis in assessing the potential of Pinus elliottii x Pinus caribaea hybrids to develop populations for genetic improvement - Tambarussi, Evandro Vagner; Marques, Emanuelli Granetto; Pedrassani Andrejow, Gisela Maria; Bandeira Peres, Fabiana Schmidt; Pereira, Fernanda Bortolanza [UNESP] (Ipef-inst Pesquisas Estudos Florestais, 2018)
One of the difficulties faced in forest tree improvement programs is the length of the cycle required for genetic selection of superior material in quality and productivity; a problem that can be solved through early selection of hybrids. The objective of the present study was to estimate genetic parameters related to silvicultural traits and verify the feasibility of early selection in Pinus elliottii x Pinus caribaea hybrids aiming to form a breeding population. The experiment was established using a randomized complete block design, with six blocks, linear plots of six plants and 24 treatments (21 pollinated progenies and three controls). Diameter at breast height (DBH) and total height (H) were measured at the fourth and eighth year after planting. The mean squares for CGC and CEC were significant for H at four and eight years of age and for DBH at eight years of age. Significant differences between treatments indicate the existence of genetic variation and suggest the possibility of gains with selection. Genetic correlations between the characteristics and between the ages were high, ranging from 0.96 to 0.99, indicating that early selection can be an effective tool for the implementation of a breeding population of the hybrid.
Keywords: genetic improvement; genetic correlation; early selection